Marcus And Burner, America Since 1945 - Weldin, Sandra (Teaching History: A Journal of Methods, 1993)
Those who teach survey classes in American history are constantly searching for supplemental readings to compensate for deficient texts and insufficient lecture time. Clearly, there is no singular publication that satisfies everyone’s agenda, but the fifth edition of America Since 1945 by Robert Marcus and David Burner is one to be seriously considered.